Reading at university: circulating ideas (Práxis Educativa, 2013)
This paper presents data about reading at university, with the aim to (re)evaluate reading teaching, through the common sense ideas which permeate this practice. The study comprised two phases and had participants from Biological and Exact Sciences, and involved especially students from four courses of Human Sciences. In phase I, the common sense circulating ideas about reading were mapped, aiming to build theme nuclei to be explored in phase II. In the latter, the blocks of questions covered themes such as: reading, reading and writing, internet, diversified sources, reading nowadays and 20 years ago and the implication of methods in the reading/writing learning processes. The methodology, mainly qualitative, has an exploratory character, with elements of discourse analysis. Results indicate that the university plays an important role when it comes to reading, and, on the other hand, there are spaces to be occupied by it, which could lead to further contribution to the continuous development of readers. Keywords: Reading at university. Reader development. Circulating ideas about reading.